TESTICULAR YOLK SAC TUMOR IN AN ONE- YEAR AND SEVENT- MONTHS OLD - Nadirah Rasyid Ridha; Farid Huzein; Emir Amal (Universitas Negeri Gorontalo, 2022)
Background: Yolk sac tumor (YST), which most frequently arises in the gonads as a type of germ cell tumor, is rare in children but is highly malignant. He most common testicular tumor in young children under the age of 3 is yolk sac tumor, and it is also known as infantile embryonal carcinoma. Case Presentation: We present the clinical future YST in an one- year and sevent-months old. In this report, we described testicular of YST in terms of the clinical manifestation, imaging, and histopathology findings, diagnosis and treatment. It has been suggested that alpha-fetoprotein (AFP) can be applied as a feasible tumor marker because its level was elevated in 90% of YST. The treatment generally involves debulking surgery of tumors followed by systemic chemotherapy. Conclusion: Our case report has a good prognosis because good responds with chemotherapy. Although YST is rare in children, pediatric physicians should be aware of this and prompt treatment should be addressed.Keywords: yolk sac tumor, chemotherapy, pediatric